Modeling Expenditure on Services for the Visegrad Group Countries - Mateusz JANKIEWICZ; Michał Bernard PIETRZAK; Elżbieta SZULC (Communications of International Proceedings, 2020)
The paper concerns the expenditure on services in the Visegrad Group countries. The aim is to analyze the differentiation in the level of these expenses in the period of 1995-2016. In the study, the Working-Leser model extended to quadratic form by Blundell, Pashardes and Weber (1993) was used. The choice of this form of the model was dictated by the possibility of indicating on its basis the level of disposable income at which services change their character from a higher-order good to a basic good. Based on the model estimation results, the income elasticity of demand for services for each country from the Visegrad Group was calculated. Assessment of the formation of the income elasticity value over time allowed to proceed with the analysis of changes in the nature of services in each country. In addition, this paper deals with the problem of the unification of the nature of goods connected with services in the analyzed countries. The σ-convergence concept was used to assess the unification process. The analysis of the coefficient of variation of the income elasticity of demand for the considered category of goods over time allowed to estimate the degree of uniformity. The downward trend in the variation coefficient shows that the value of elasticity is becoming more uniform among countries, and consequently the nature of services is becoming similar.
Keywords: Household Expenditure on Services; Income Elasticity of Demand; Process of Unifying the Nature of Services.